BAS/BSCR38 Cytokine profiling in culture reveals a predominance of M1 macrophage polarisation in symptomatic carotid plaques. Issue 17 (26th August 2010) - Shalhoub, J; Cross, A; Allin, D; Essex, D; Davies, A H; Monaco, C
Abstract : Rationale: Macrophages in atherosclerotic plaques are a heterogeneous population. To uncover signatures of classical (M1) or alternative (M2) macrophage polarisation during plaque instability, we compared cytokine and chemokine production via Luminex profiling in asymptomatic human carotid plaques with carotid plaques in the territory of recent focal neurological symptomatology. Methodology: Carotid endarterectomy specimens were collected from 50 consenting patients (26 symptomatic, 24 asymptomatic). Fresh specimens were divided symmetrically along their long axis, allowing for representative undertaking of both immunohistochemistry and plaque cell culture (Monaco et al. PNAS USA 2004;101 :5634–9). Automated image analysis (Clemex Vision) quantified CD68 staining. Cells were isolated via enzymatic dissociation to produce a viable mixed cell suspension and cultured for 24 h. Macrophage was the predominant cell type in the mixed cell culture. Supernatants were interrogated with a panel of 22 cytokines and chemokines on a Luminex 100 platform. Results: CD68 immunopositivity was significantly higher in symptomatic than in asymptomatic plaques (p=0.0075). Luminex detected 17 of the 22 analytes, with a predominance of myeloid-derived cytokines over lymphoid-derived cytokines, in keeping with the predominance of macrophage in culture. Tumour necrosis factor α, interleukin (IL)-1α, IL-1β, IL-6, granulocyte-macrophage colony-stimulating factor, CCL2, CCL5 and IL-10 levels were significantly higher in symptomatic plaques. Conclusions: Our data demonstrate that symptomatic atherosclerotic carotid disease is associated with a cytokine pattern consistent with the predominance of proinflammatory M1-type macrophage polarisation. M2-dependent cytokine IL-10 was also part of this inflammatory response, suggesting macrophage heterogeneity. Our study has implications for future therapeutic and diagnostic applications for high-risk atherosclerosis.